To Go Global or Stay Local: that is the question ... - Syed Fadzil, Sharifah Fairuz (MAJ - Malaysia Architectural Journal, 2021)
By : Assoc. Prof. Ar. Dr. Sharifah Fairuz Syed Fadzil, School of Housing Building and Planning, Universiti Sains Malaysia, Penang Shakespeare said “To be or not to be that is the question”……“To go global or to stay local” is something else……. But it does sound similar…. And this is something practicing architects need to ponder on as well”. In this short article, allow me to share just the “verbatim” part of the study to you, as the “focused” group of architects reading this AM magazine. “Verbatims” are the exact same words that come from the architects, which can be considered as important themes in a thematic analysis contributing to the study. Here are some of the verbatims and themes with R1 – R17 indicating which architects they came from. From all the interviews which had to be transcribed and analyse, the themes are derived as repeated points which most architects, though interviewed separately, seem to say the same thing but in different ways. Themes therefore indicate the significance of the points as they come from the views of more than at least 4 of the architects interviewed.